Environmentally benign smart self-healing silicone-based coating with dual antifouling and anti-corrosion properties. (August 2022) - Sun, Jiawen; Duan, Jizhou; Liu, Xiangju; Dong, Xucheng; Zhang, Yimeng; Liu, Chao; Hou, Baorong
Highlights: The coating was prepared with the functionalized monomer "lipoic acid-benzothiazole" and lipoic acid modified PDMS based polyurea-urethane. The coating presents a strong mechanical and adhesion strength. The coating exhibits a fast and efficient self-healing property at room temperature in both air and artificial sea water. The environmentally coating without any additional toxic biocides shows efficient static fouling-resistant and anticorrosive properties. Abstract: Marine corrosion and biofouling on metallic materials are sticky problems in maintenance of various vessels and facilities in the ocean. Further, designing of an eco-friendly marine coating with both antifouling and anti-corrosion properties has remained a significant challenge in marine field. The present study aimed to develop a novel smart self-healing silicone-based coating with dual antifouling and anti-corrosion properties was through disulfide exchange reaction between the functionalized monomer "lipoic acid-benzothiazole" (LA-BTZ) and LA modified polydimethylsiloxane (PDMS) based polyurea-urethane (PDMS-PUU-LA). Multiple dynamic bonds in backbone, flexible disulfide bonds, and strong cross-linked hydrogen bonds ensure the PDMS-based polymer with good toughness (2.58 MPa of ultimate strength), high stretchability (1014.7%), and self-healing properties. It was found that the scratches on the film in air completely disappeared within 40 min at room temperature. The time required for the healing efficiency of strength ranged between 98.5 and 94.6% under ambient condition and artificial seawater was only 4 and 8 h, respectively. The adhesion strength of silicon-based coating to epoxy resin and steel substrate was ∼ 2.50 and ∼ 3.33 MPa, respectively. In addition, results of laboratory bioassays and marine field test of 120-day demonstrated that coating without any additional toxic biocides in the present study had long-term static fouling-resistant properties. Electrochemical impedance spectroscopy (EIS) measurements and salt spray test showed that the PDMS-PUU-TZ-3 coating exhibited the better corrosion resistance. Therefore, the current work presented a novel eco-friendly smart silicone-based coating for marine antifouling and anti-corrosion. Graphical abstract: Image, graphical abstract .